The Influence of Marketing Mix Strategy on Bread Customer Satisfaction in Nigerian Market - Ige Ohimain Ozumba; Elemo Okon (Journal of Economics Business Industry, 2023)
Bread is a practical and ready-to-eat food. Urban people consume Bread as a breakfast menu. This causes the bakery industry to grow even more. This study aims to analyze the purchasing decision process, analyze the dimensions in the marketing mix that affect consumer satisfaction, analyze the level of satisfaction formed by the marketing mix and formulate managerial implications from the results of the marketing mix analysis. Data were obtained from 120 respondents determined by convenience sampling and analyzed using the Structural Equation Model. The results showed that consumers go through all stages of the purchase decision process. Consumers buy Bread based on the motivation to meet their needs as a substitute for rice. Consumers obtain information about Bread from advertising. The main evaluation criterion for consumers before deciding on the purchase of Bread is the condition of the Bread. The consumer's purchase plan depends on the situation. If the variety of types of Sari Roti sought is not available, and there is a price increase, the consumer's action is still to buy Bread. However, if another brand of Bread provides a discount, consumers switch to that other brand of Bread during that period only. Marketing mix has a positive and significant effect on consumer satisfaction. This shows that the role of product, price, place and promotion increases customer satisfaction. The dimensions of product and price have a more substantial influence than place and promotion. The level of customer satisfaction of Sari Roti is in the very satisfied category. The recommended managerial implications are increased availability, 24-hour sales, public relations and sales promotion.